2010
DOI: 10.4161/cc.9.19.13385
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and epigenetic control of cellular differentiation

Abstract: In mammals the genome is shaped by epigenetic regulation to manifest numerous cellular identities. The term epigenetics has been used to refer to changes in gene expression, which are heritable through multiple cell division cycles that are not due to variations in primary DNA sequence. Stable suppression of differentiation genes is required to sustain the undifferentiated state in cells ranging from embryonic stem cells to somatic stem cell progenitors that constantly replenish self-renewing tissues. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 35 publications
2
96
0
1
Order By: Relevance
“…Neither can it provide data on the molecular mechanisms underlying the effects of alcohol and smoking on global DNA methylation. Also, DNA methylation patterns are frequently tissue-and cell-specific, reflecting tissue-specific regulation of DNA methylation (Khavari, Sen, & Rinn, 2010). Therefore, methylation patterns should ideally be examined in the tissue that is directly related to the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Neither can it provide data on the molecular mechanisms underlying the effects of alcohol and smoking on global DNA methylation. Also, DNA methylation patterns are frequently tissue-and cell-specific, reflecting tissue-specific regulation of DNA methylation (Khavari, Sen, & Rinn, 2010). Therefore, methylation patterns should ideally be examined in the tissue that is directly related to the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment and maintenance of cellular identity following differentiation from pluripotent cell types is dependent on global epigenetic changes that 'landscape the genome' to streamline specific functional programs and maintain a specified cell-lineage fate (Khavari et al, 2010). Differentiation of ESCs and iPSCs towards stable mesenchymal lineages is dependent on changes in DNA methylation of CpG islands that result in characteristic methylation profile that can be used to distinguish specific cells from normal and diseased states (Fernandez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The DNA methylation status of specific CpG dinucleotides provide markers of cell differentiation in diverse types of mammalian cells, 1 including those of the haematopoietic system. 2,3 Our earlier experiments showed that cell lineage-specific differentially methylated regions (DMRs) distinguish normal human leukocyte subsets and can be used to detect and quantify these subsets in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%